Post-carotid Endarterectomy Hypertension. Part 2: Association with Peri-operative Clinical, Anaesthetic, and Transcranial Doppler Derived Parameters. (November 2017) - Newman, Jeremy E.; Bown, Mathew J.; Sayers, Robert D.; Thompson, Jonathan P.; Robinson, Thompson G.; Williams, Bryan; Panerai, Ronney; Lacy, Peter; Naylor, A. Ross
Abstract : Objective/Background: The first paper in this series observed that pre-operative baroreceptor dysfunction and poorly controlled hypertension were independently predictive for identifying patients who went on to require treatment for post-endarterectomy hypertension (PEH). The second paper examines the influence of intra-operative patient, transcranial Doppler (TCD) ultrasound, and anaesthetic variables on the incidence of PEH. Methods: In total, 106 patients underwent carotid endarterectomy (CEA) under general anaesthesia. Systolic blood pressure (SBP) changes, anaesthetic and vasoactive agents, analgesia, and post-operative pain scores, as well as TCD derived changes in middle cerebral artery (MCA) velocity during surgery were recorded. Patients who met pre-existing unit criteria for treating PEH after CEA (SBP > 170 mmHg without symptoms or SBP > 160 mmHg with headache/seizure/neurological deficit) were treated according to an established and validated protocol. Results: In total, 40/106 patients (38%) required treatment for PEH following CEA (26 in theatre recovery [25%], 27 back on the vascular surgery ward [25%]), whereas seven (7%) had SBP surges > 200 mmHg on the ward. Patients requiring treatment for PEH had significantly higher pre-induction SBP (174 ± 21 mmHg vs. 153 ± 21 mmHg; p  < .001), the greatest decreases in SBP after induction of anaesthesia (median decrease 100 ± 32 mmHg vs. 83 ± 24 mmHg; p  = .01) and were significantly more likely to experience moderate/severe pain scores post-operatively ( p  = .003). Logistic regression analysis of the pre- and intra-operative data revealed that higher pre-induction mean SBP and lower pre-operative (impaired) BRS were the only independent predictors of PEH. Conclusion: This analysis of intra-operative variables has demonstrated that patients with poorly controlled and/or labile hypertension at induction of general anaesthesia were those at greatest risk of requiring treatment for PEH in the post-operative period after CEA. No other variables, including use of vasopressors, treatment of hypotension, anaesthetic agents, or changes in MCA velocity after clamp release and restoration of flow were able to predict who might go on to require treatment for PEH. Identification of at-risk individuals and aggressive blood pressure control in the post-operative period remains the mainstay of treatment.